Effect of antibacterial agents on the surface hardness of a conventional glass-ionomer cement (Journal of Applied Oral Science, 2012)
In atraumatic restorative treatment (ART), caries removal with hand excavation instruments is not as efficient as that with rotary burs in eliminating bacteria under the glass ionomer cements (GICs). Thus, different antibacterial agents have been used in recent studies to enhance the antibacterial properties of the GICs, without jeopardizing their basic physical properties. OBJECTIVE: The objective of this study was to evaluate the effect of antibacterial agents on the surface hardness of a conventional GIC (Fuji IX) using Vickers microhardness [Vickers hardness number (VHN)] test. MATERIAL AND METHODS: Cetrimide (CT), cetylpyridinium chloride (CPC) and chlorhexidine (CHX) were added to the powder and benzalkonium chloride (BC) was added to the liquid of Fuji IX in concentrations of 1% and 2%, and served as the experimental groups. A control group containing no additive was also prepared. After the completion of setting reaction, VHN measurements were recorded at 1, 7, 15, 30, 60, and 90 days after storage in 37°C distilled water. A one-way ANOVA was performed followed by a Dunnett t test and Tamhane T2 tests and also repeated measurements ANOVA was used for multiple comparisons in 95% confidence interval. RESULTS: VHN results showed significant differences between the control and the experimental groups at all time periods (p